2006
DOI: 10.1371/journal.pmed.0030334
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokines as Risk Factors for a First Venous Thrombosis: A Prospective Population-Based Study

Abstract: BackgroundIn case-control studies, elevated levels of interleukins 6 and 8 have been found to be associated with an increased risk of venous thrombosis (VT). Because of the design of these studies, it remained uncertain whether these alterations were a cause or a result of the VT. In order to distinguish between the two, we set out to measure the levels of six inflammatory markers prior to thrombosis in a population-based cohort using a nested case-cohort design.Methods and FindingsBetween August 1995 and June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 30 publications
1
63
1
1
Order By: Relevance
“…Further, two case-control studies with discrepant results have been reported for noncancer patients. In patients without cancer, Christiansen et al [33] found no correlation between elevated levels of IL-6, IL-8, IL-10 and IL-1β and incidence of venous thromboembolic events. Van Aken et al [34] reported that increased IL-8 levels (>90th percentile) were associated with a 1·9-fold increased risk for thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Further, two case-control studies with discrepant results have been reported for noncancer patients. In patients without cancer, Christiansen et al [33] found no correlation between elevated levels of IL-6, IL-8, IL-10 and IL-1β and incidence of venous thromboembolic events. Van Aken et al [34] reported that increased IL-8 levels (>90th percentile) were associated with a 1·9-fold increased risk for thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study of the same subjects as in our investigation we found no associations between venous thrombosis and the inflammatory cytokines interleukin (IL)1β, IL-6, IL-8, IL-12p70, and tumor necrosis factor-α, even in a short time perspective. 31 The reason for this might be that single cytokines are less sensitive parameters than CRP for demonstrating subclinical inflammation, or that the level of sensitivity of the methods used to analyze cytokines and CRP differs. We found no statistically significant correlation between CRP and these cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…23 Therefore, it cannot be excluded that the reported relationships between inflammation and VTE are in part the result of VTE rather than the cause.…”
Section: Innate and Acquired Immunitymentioning
confidence: 99%